Răspuns :
16-6×4÷[13×2-1×8-(20×1-5×a)]+3×6=31
16-6×4÷[13×2-1×8-(20-5×a)]+3×6=31
16-6×4÷(26-8-20-5×a)+3×6=31
16-6×4÷(18-15×a)+3×6=31
16-6×4÷(13×a)+18=31
16-6×4÷13×a+18=31
40÷13×a+18=31
3×a+18=31/-18
3×a=13/÷3
a=10
16-6×4÷[13×2-1×8-(20-5×a)]+3×6=31
16-6×4÷(26-8-20-5×a)+3×6=31
16-6×4÷(18-15×a)+3×6=31
16-6×4÷(13×a)+18=31
16-6×4÷13×a+18=31
40÷13×a+18=31
3×a+18=31/-18
3×a=13/÷3
a=10
16 - 6 * 4 : [13 * 2 - 1 * 8 - (20 * 1 - 5* a)] + 3 * 6 = 31
16 - 24 : [26 - 8 - (20 - 5a)] = 31 - 18
16 - 24 : [18 - (20 - 5a)] = 13
24 : [18 - (20 - 5a)] = 16 - 13
24 : [18 - (20 * 5a) = 3
18 - (20 - 5a) = 24 : 3
18 - (20 - 5a) = 8
20 - 5a = 18 - 8
20 - 5a = 10
- 5a = 10 - 20
a = 20 : 5
a = 4
16 - 24 : [26 - 8 - (20 - 5a)] = 31 - 18
16 - 24 : [18 - (20 - 5a)] = 13
24 : [18 - (20 - 5a)] = 16 - 13
24 : [18 - (20 * 5a) = 3
18 - (20 - 5a) = 24 : 3
18 - (20 - 5a) = 8
20 - 5a = 18 - 8
20 - 5a = 10
- 5a = 10 - 20
a = 20 : 5
a = 4